2015
DOI: 10.18404/ijemst.10740
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Physics Reasoning in Face-to-Face and Online Forum Collaboration Around a Digital Game

Abstract: Students playing digital learning games in the classroom rarely play alone, even in digital games that are ostensibly "single-player" games. This study explores the patterns of physics reasoning that emerge in face-toface and online forum collaboration while students play a physics-focused educational game in their classroom. We observed five increasing levels of explicit articulation of physics reasoning across interactions in the face-toface and online forum interactions. Additionally, we found that students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 62 publications
(38 reference statements)
1
20
0
4
Order By: Relevance
“…We refer to this as a "sense-making orientation." We have observed related patterns in studies with other games (e.g., [17]). …”
Section: External Scaffoldssupporting
confidence: 57%
See 1 more Smart Citation
“…We refer to this as a "sense-making orientation." We have observed related patterns in studies with other games (e.g., [17]). …”
Section: External Scaffoldssupporting
confidence: 57%
“…Additionally, providing collaboration opportunities between peers during game play can serve as a productive external scaffold that allows students to leverage discourse in order to negotiate meaning of concepts and actions within games, construct ideas, resolve conflicts, etc. [16,17]. In the context of the current study, although most students used internal scaffolds in some way to assist their game play, many also found that these scaffolds were not enough to get through challenges.…”
Section: Internal and External Scaffoldsmentioning
confidence: 80%
“…The low critical thinking skills in theory can be caused by: motivation, lack of responsibility, low analytical skills, and lack of discipline in learning (Adebayo, 2014). This can also be due to a lack of ability to organize time, lazy to learn, and less supportive learning environments (Chakravarthi, 2010;Eaton, 2015). The low critical thinking skills of pre-service physics teacher are suspected to have something to do with the teaching process that is implemented.…”
Section: The Effectiveness Of Or-ipa Model Pbl Model and Conventionmentioning
confidence: 99%
“…The low critical thinking skills are theoretically caused, among other things, by: poor motivation and responsibility, poor analytical skills, and less discipline in teach (Adebayo, 2014). This is also due to the lack of ability to organize time, lazy to learn, and less supportive learning environment (Chakravarthi, 2010;Eaton, 2015). Therefore, it is necessary to compare the effectiveness between OR-IPA Model and PBL Model in improving student critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Al adoptar este enfoque, se argumenta a favor de la importancia de evaluar la relación del estudiante con el videojuego [54], donde el resultado obtenido mediante encuestas muestra que estas metodologías pintan una imagen más clara y proporcionan conocimientos sobre el diseño de nuevas herramientas para enseñar a la próxima generación [55].…”
Section: Ventajas De Los Videojuegos En La Educaciónunclassified